The Influence of Twice Brand Ambassador and Korean Wave on Scarlett Product Purchase Decisions With Brand Image as a Mediating Variable - Valepi, Dinda Ayu; Rahmidani, Rose (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2025)
In recent years, the beauty industry has grown rapidly due to increasing public awareness of self-care and appearance. Demand for skincare and body care products has risen as consumers seek to boost their confidence. To meet these needs, companies must continue developing unique products to stay competitive. One strategy is using famous figures as brand ambassadors, as their popularity helps spread the brand’s message more widely. For example, Scarlett appointed TWICE, a South Korean girl group from JYP Entertainment, as its brand ambassador. However, this decision sparked controversy, with some consumers accusing Scarlett of skin color discrimination. This research examines the impact of TWICE as a Brand Ambassador and the Korean Wave on consumers’ purchasing decisions regarding Scarlett products, with Brand Image as a mediating variable. The study adopts a quantitative and associative research design. The target population consists of students at Padang State University familiar with both Scarlett products and TWICE. Using purposive sampling, 100 respondents were obtained. Data was collected through questionnaires and analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0 software. The findings shed light that Brand Ambassador and Korean Wave significantly influence Brand Image; Brand Image significantly affects Purchasing Decisions; both Brand Ambassador and Korean Wave directly influence Purchasing Decisions; and both have indirect effects on Purchasing Decisions through Brand Image. These findings contribute to understanding celebrity endorsement and consumer behavior in global cultural trends. Practically, companies should carefully choose brand ambassadors and use cultural trends to boost the brand's image and drive sales.